Applicability of handmade expanded polytetrafluoroethylene trileaflet-valved conduits for pulmonary valve reconstruction: An ex vivo and in vivo study - Kan, Chung-Dann; Wang, Jieh-Neng; Chen, Wei-Ling; Lu, Pong-Jeu; Chan, Ming-Yao; Lin, Chia-Hung; Hsieh, Wan-Chin (The Journal of thoracic and cardiovascular surgery, 2018)
OBJECTIVE: The handmade expanded polytetrafluoroethylene (ePTFE) trileaflet-valved conduit could potentially be used as a substitute pulmonary valve replacement material, especially in children. The current study investigated (1) the function of the ePTFE trileaflet-valved conduits in an ex vivo experimental system and (2) the short-term performance of the conduit in a porcine model to verify its clinical applicability. METHODS: The competency of the ePTFE trileaflet-valved conduits was estimated through ex vivo (using a pulmonary mock circulation loop) and in vivo (in a porcine model with a damaged pulmonary valve) experiments. Explants were examined by gross morphology and histopathologic examination. RESULTS: In the ex vivo experiment, the ePTFE trileaflet-valved conduits were determined to effectively increase mean pulmonary pressure from 10.2 to 14.4 mm Hg compared with defective silicon-valved conduits. In addition, the regurgitation fraction value of ePTFE trileaflet-valved conduits was 15.9% to 18.1%, which was significantly better than the defective valve conduits (regurgitation fraction = 73.5%-85.7%). In the in vivo experiment, the valved conduits were confirmed to be with good valve position maintenance, and the valve and leaflets showed no signs of thickening or peeling after a short-term implantation period. There were also no significant signs of inflammation reaction on histopathologic examination. CONCLUSIONS: The ePTFE trileaflet-valved conduits for pulmonary valve reconstruction showed acceptable performance and outcomes in the ex vivo and in vivo experiments. The ePTFE trileaflet-valved conduit may be clinically useful, although additional studies in animals should be conducted to determine its long-term outcomes.
Keywords: Prosthesis Design; Polytetrafluoroethylene; Device Removal; ePTFE trileaflet-valved conduits; Time Factors; Pulmonary Valve; pulmonary valve reconstruction; Heart Valve Prosthesis; plicní chlopeň; Sus scrofa; modely u zvířat; chirurgická náhrada chlopně; protézy - design; porcine model; Heart Valve Prosthesis Implantation; zvířata; Hemodynamics; odstranění implantátu; srdeční chlopně umělé; hemodynamika; časové faktory; polytetrafluoroethylen; testování materiálů; Materials Testing; Models, Animal; Animals